Baroclinic transport variability of the Antarctic Circumpolar Current south of Australia (WOCE repeat section SR3) - Rintoul, Sr; Sokolov, S (Journal of Geophysical Research: Oceans, 2001)
Baroclinic transport variability of the Antarctic Circumpolar Current (ACC) near 140 degreesE is estimated from six: occupations of a repeat section occupied as part of the World Ocean Circulation Experiment (WOCE section SR3). The mean top-to-bottom volume transport is 147+/-10 Sv (mean +/-1 standard deviation), relative to a deep reference level consistent with water mass properties and float trajectories. The location and transport of the main fronts of the ACC are relatively steady: the Subantarctic Front carries 105+/-7 Sv at a mean latitude between 51.0 and 52 degreesS; the northern branch of the Polar Front carries 5+/-5 Sv to the east between 53 degrees and 54 degreesS; the southern Polar Front carries 24+/-3 Sv eastward at 59 degreesS; and two cores of the southern ACC front at 62 degrees and 64 degreesS carry 18+/-3 and 11+/-3 Sv, respectively. The variability in net property transports is largely due to variability of currents north of the ACC, in particular, an outflow of 8+/-13 Sv of mater from the Tasman Sea and a deep anticyclonic recirculation carrying 22+/-8 Sv in the Subantarctic Zone. Variability of net baroclinic volume transport is similar in magnitude to that measured at Drake Passage. In density layers, transport variability is small in deep layers, but significant (range of 4 to 16 Sv) in the Subantarctic Mode Water. Variability of eastward heat transport across SR3 is significant (range of 139 degreesC Sv, or 0.57 x 10(15) W, relative to 0 degreesC) and large relative to meridional heat flux in the Southern Hemisphere subtropical gyres. Heat transport changes are primarily due to variations in the westward flow of relatively warm water across the northern end of the section. Weak (strong) westward flow and large (small) eastward heat flux coincides with equatorward (poleward) displacements of the latitude of zero wind stress curl.